Objectification Theory and Psychology of Women: A Decade of Advances and Future Directions - Moradi, Bonnie; Huang, Yu-Ping (Psychology of women quarterly, 2008)
Fredrickson and Roberts (1997) proposed objectification theory as an integrative framework for understanding how women's socialization and experiences of sexual objectification are translated into mental health problems. This article reviews the past decade of research grounded in objectification theory and highlights needed directions for future scholarship in this area. Specifically, this article reviews research organized according to the following themes: (a) self-objectification and its proposed consequences, (b) sexual objectification experiences as a proposed precursor, and (c) disconnections from bodily functions. An overview of emerging objectification theory research with men is also provided. The review concludes with needed directions for future theoretical and research efforts aimed to advance the psychology of women.